IP address management - Rooney, Timothy, 1962-; Dooley, Michael, 1962- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
"This new edition discusses IP address management (IPAM) needs and methods that have evolved over the past decade. Such evolution includes mainstream use of private and public cloud services, maturation of IPv6 implementations, increased interest in DNS security approaches, and proliferation of Internet of Things (IoT) devices. These broad trends are serving to broaden the IPAM purview of network managers. The book begins with a basic overview of IP networking, including a discussion of protocol layering, addressing, and routing. After a review of the IP address management (IPAM) technologies, the book introduces the major components, motivation, benefits, and basic approaches of IPAM"--
DNS Update Messages 314 -- DNS Extensions (EDNS0) 316 -- The DNS Resolution Process Revisited 319 -- DNS Resolution Privacy Extension 325 -- DNS Resolver Configuration 326 -- DNS Applications and Resource Records 327 -- DNS Resource Record Summary 362 -- Chapter 20 RFC Reference 368 -- IPv4 Protocol RFCs 368 -- IPv6 Protocol RFCs 368 -- IPv4/IPv6 Co-Existence RFCs 370 -- IP Address Management RFCs 372 -- DHCP Protocol RFCs 373 -- DHCPv6 Protocol RFCs 376 -- DNS Protocol RFCs 377 -- DNSSEC RFCs 381 -- Non-DNSSEC DNS Security-related RFCs 382 -- DNS ENUM-related RFCs 383 -- Management or Operational RFCs 384 -- Chapter 21 Glossary 385 -- Chapter 22 References 386.
Timothy Rooney appears as the first named author in the first edition.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 18, 2022).
John Wiley and Sons
Keywords: Internet addresses; Internet domain names; Adresses Internet; Internet addresses; Internet domain names